Pedagogy of the History Classroom - Lancaster, Scott (2018)
The purpose of this study is to uncover what specific role constructivist pedagogy has within the history classroom, and whether it is perceived as useful from both a student and teacher perspective, to best inform future history teaching practice. The study was conducted within four secondary schools across the south and east of England, focussing on students in both years 7 and 10. The research process involved lesson observations, questionnaires and interview process to uncover perceptions, reflections and opinions regarding the implementation of constructivism in secondary history classrooms.